SOSIALISASI DIGITAL MARKETING ERA 5.0 BAGI PEMUDA KELURAHAN RIMBA SEKAMPUNG-BENGKALIS RIAU - Fanalisa Elfa; Halim Dwi Putra; Desi Wahana (LPPM Universitas Bina Bangsa, 2023)
Digital Marketing Era 5.0 is a way of marketing that integrates digital technology and analytics to help companies optimize their marketing strategy. Era 5.0 focuses on increasing interaction between companies and customers through social media, search engines, and online advertising for this reason which is the main factor for this service to be held. By integrating digital technologies, businesses can improve campaign efficiency and create stronger relationships with customers. The purpose of this service is held so that youth in Rimba Sekampung Village can take advantage of this digital era to promote the products and services they offer, build community, and improve their overall marketing. The method used is socialization and digital training in the village of Jungle and Village. The conclusion of this dedication is that Digital Marketing Era 5.0 Socialization for Rimba Sekampung Kelurahan Youth is designed to help them increase their knowledge of how to use digital media to increase sales and income. It will also teach them how to leverage digital technology to build a marketing network and achieve their business goals